Historisch-vergleichende Betrachtungen zum ethnopädagogischen Wirken des tschuwaschischen Aufklärers Iwan Jakowlew und des deutschen Reformators Martin Luther - Tolstova, Elena Vladimirovna (International Dialogues on Education Journal, 2015)
This article deals with ethnopedagogical orientations in the work of the reformer Martin Luther and the Chuvash enlightener Iwan Jakowlew. They played a fundamental role in the development of a national identity of their people and addressed a number of themes that are still relevant today. The National cultures were, both in Russia and in Germany, under pressure, even from a linguistic point of view. The Russian orthodox Christianity insisted on Russian as the language of religious instruction; in German churches was preached in Latin. There are many similarities in the work of these two eminent representatives of the German and Chuvash people with respect to a national literary language, the introduction of native languages in schools, education being connected with meaningful tasks, music education, education of families, women’s education, etc., despite their distance of three centuries and almost 3,000 km. This points to the continuity and general validity of certain pedagogical insights and experiences and the possibility that these may be a useful topic of study for the respective national culture and education.